2009
DOI: 10.1017/s1368980008003674
|View full text |Cite
|
Sign up to set email alerts
|

Food patterns and Mediterranean diet in western and eastern Mediterranean islands

Abstract: Objective: To assess current Mediterranean dietary patterns (MDP) in the western and eastern Mediterranean, i.e. in Balearic islanders (BI) and Greek islanders (GI). Subjects and methods: Dietary patterns were assessed using FFQ on a representative sample (n 1200) of the BI and GI (n 1324) adult population. A Mediterranean Diet Score (MDS) was calculated according to the consumption of nine MDP components: (i) with a beneficial effect on health, i.e. vegetables, fruits and nuts, cereals, legumes, fish and shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 51 publications
2
13
0
3
Order By: Relevance
“…However, in many cases, self-reporting is the only feasible method of assessing dietary intake in epidemiological studies. Over the years, researchers have come to recognise that the dietary assessment method used (FFQ) usually tends to overestimate food and nutrient intake, and the report values from FFQ are subject to substantial error, both systematic and random [42]. Nevertheless, taking into account the well-known limitations of the use of FFQ, we agree with the opinion of previous authors [42][43][44] who defend the use of FFQ with firm and clear statements.…”
Section: Strengths and Limitationssupporting
confidence: 79%
“…However, in many cases, self-reporting is the only feasible method of assessing dietary intake in epidemiological studies. Over the years, researchers have come to recognise that the dietary assessment method used (FFQ) usually tends to overestimate food and nutrient intake, and the report values from FFQ are subject to substantial error, both systematic and random [42]. Nevertheless, taking into account the well-known limitations of the use of FFQ, we agree with the opinion of previous authors [42][43][44] who defend the use of FFQ with firm and clear statements.…”
Section: Strengths and Limitationssupporting
confidence: 79%
“…The definition of a Mediterranean diet places nuts up front and demands their intake on a daily basis, together with vegetables, fruit, olive oil and cereals [ 21 ]. Unfortunately, such intense consumption is not common, even among populations of the Mediterranean region [ 22 , 23 , 24 ]. A recent study performed in the population of Dalmatia, in the coastal region of Croatia, revealed a disappointingly low prevalence of daily nut consumption, ranging from 3% on the Island of Vis to 11% in the City of Split [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, obesity rates in Greece show an increased tendency, with higher rates of obesity and lower rates of adherence to MD in women, especially of younger reproductive age [11]. Evidence supports that more and more Mediterranean countries have abandoned MD principles [29]. For these reasons, during this period, when protective effect of MD is lost, more and more studies from the Mediterranean area will focus on the results of the above-mentioned phenomenon and will demonstrate its impact on public health.…”
Section: Discussionmentioning
confidence: 98%